Gender Interpretation in the Qur'an: A Critical Examination of Verses Relating to Domestic Violence - Sigit Abdulloh; Edi; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to critically examine the verses of the Koran which are often associated with domestic violence (KDRT) and how gender interpretation can influence the interpretation of these verses. The main question of this research is how verses related to domestic violence are interpreted from a gender perspective, and to what extent these interpretations support or reject violence in domestic relationships. The research method used is a literature study with a hermeneutic approach and gender analysis. This research found that contextual interpretations that consider gender justice are more supportive of protecting women's rights and rejecting all forms of domestic violence. These results show that an inclusive and gender-just understanding in interpreting the Koran can contribute to efforts to reduce domestic violence in society.